Geôle, enjôler, enjoliver : surveiller et (p)unir dans Lolita - René Alladaye (Sillages Critiques)
Nabokov writes in “On a book entitled Lolita” that the “initial shiver of inspiration” that triggered the composition of the novel was prompted by a newspaper story about an ape in the Jardin des Plantes which had produced a drawing representing the bars of its cage. This study simply takes him at his word and explores the theme of custody in Lolita. It tries to show that this notion dominates the Nabokov’s novel, both in terms of plot and narrative, and affects considerably our reception of the book, turning the reader into the captive of a singularly sophisticated textual mechanism.